Effect of a Cognitive Behavioral Self‐Help Intervention on Depression, Anxiety, and Coping Self‐Efficacy in People With Rheumatic Disease. Issue 7 (1st July 2013) - Garnefski, N.; Kraaij, V.; Benoist, M.; Bout, Z.; Karels, E.; Smit, A.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate whether a new cognitive–behavioral self‐help program with minimal coaching could improve psychological well‐being (depression, anxiety, and coping self‐efficacy) in people with rheumatic disease and depressive symptoms. Methods In total, 82 persons with a rheumatic disease enrolled in a randomized controlled trial were allocated to either a group receiving the self‐help program or a waiting list control condition group. For both groups, measurements were done at baseline, posttest, and followup. The outcome measures were the depression and anxiety scales of the Hospital Anxiety and Depression Scale and an adaptation of the Generalized Self‐Efficacy Scale. Repeated‐measures analyses of covariance were performed to evaluate changes in outcome measures from pretest to posttest and from posttest to followup. Results The results showed that the self‐help program was effective in reducing symptoms of depression and anxiety and in strengthening coping self‐efficacy. The positive effects remained after a followup period of 2 months. Conclusion This cost‐effective program could very well be used as a first step in a stepped care approach or as one of the treatment possibilities in a matched care approach.